THE SPREAD OUT STRATEGY OF THE MAIN WEAPONS TOOL SYSTEM OF THE INDONESIAN AIR FORCE IN THE REGION OF THE REPUBLIC OF INDONESIA - Akib, Haedar; Hariyono, Umar Sugeng (AUSTRAL: Brazilian Journal of Strategy & International Relations, 2022)
The urgency of this article is based on its focus and locus on the spread out or placement a strategy of the Main Weapons Tool System (Alutsista) in the broad perspective of the territory of the Unitary State of the Republic of Indonesia (NKRI). One of the Alutsista owned by Indonesia is Air Alutsista which is used to maintain the existence of the Indonesian state in the air. The air alutsista manned by the Indonesian National Army (TNI) Air Force (AU) currently has a considerable power posture in Asia and the international world. This study aims to provide an overview of Strategy Placement Alutsista TNI AU seen from the vast territory of the Republic of Indonesia as an archipelago. This study uses normative research methods conducted by reviewing relevant reference content or based on secondary data that is adjusted with factual data of observation and experience of the author. The result of the research shows that faced with the territory of NKRI as an archipelago country, the placement of Alutsista TNI AU is uniformly distributed because it has only been fulfilled 40 percent of the minimum strength and still dominated in Java, Sumatera, Kalimantan and Sulawesi which should be fulfilled for Papua , Maluku, West Nusa Tenggara, East Nusa Tenggara, and Bali. Similarly, the deployment of Radar will be provided at least 23 units because currently placed only amounted to 20 units.